2023
DOI: 10.3390/en16166026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Gasoline—Water Mixture Fuel Impingement Preparation Method and Spray Characteristics with High Injection Temperatures and Pressures

Meng Ji,
Zhijun Wu,
Alessandro Ferrari
et al.

Abstract: Gasoline–water mixed injections are of great interest because of their advantages for reduced manufacturing costs and improved atomization, with the potential to alleviate engine detonation and reduce emissions. In this work, based on the principle of impinging flow, a real-time gasoline–water mixture preparation system for internal combustion engines was designed and the preparation system performance was compared with the standard swirl mixing technique. An image processing method was established to quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The main parameter monitored was the flow rate of water, which was then used to calculate the jet velocity of the nozzle. The Weber number and Reynolds number were calculated based on the jet diameter and jet velocity (V j ) to study the characteristics of the liquid sheet, as shown in Equations ( 1) and (2). Table 3 presents the different parameters and their operating ranges.…”
Section: Experiments Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The main parameter monitored was the flow rate of water, which was then used to calculate the jet velocity of the nozzle. The Weber number and Reynolds number were calculated based on the jet diameter and jet velocity (V j ) to study the characteristics of the liquid sheet, as shown in Equations ( 1) and (2). Table 3 presents the different parameters and their operating ranges.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…Spray and atomization are commonly employed in various industry applications, including printing [1], combustion [2], drying [3], and agriculture [4]. Among the different techniques for liquid-jet breakup, jet impact atomization stands out due to its simplicity and cost-effective manufacturing process that guarantees efficient atomization.…”
Section: Introductionmentioning
confidence: 99%